Sistem Kunci Pintar (Smart Lock System) Berbasis QR-code - Luthfi Afif; Yusnita Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
This research is proposed to design a smart lock system by using QR Code scanning as a key in the locker. The device system design consists of ESP8266 Node MCU module, 12V Power Switch Adapter, AMS 1117 module with 3.3V and 5V output voltages, three pieces of 5V Relays, and three pieces of 12VSolenoids. The design of database uses a web hosting database server. The results showed that each components can work properly and the MySQL database has many tables and each tables containspersonal data from admins and students. Then in terms of security systems, the login level status and user verification were added to the tables. the login level will active when a student fails to login more thanthree times, the database will automatically block the account and send an email notification to the user. This aims to protect the account from irresponsible parties when accessing the locker. Meanwhile, userverification is intended to validate the student's personal data by using their student ID card (KTM).Keywords : Smart Lock System, QR-code , Solenoid , MySQL